All Days 2009
DOI: 10.2118/124677-ms
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Roles of Inflow-Control Devices in Optimizing Horizontal-Well Performance

Abstract: Inflow Control Device, often referred to as equalizer, is a completion hardware that is deployed as a part of well completions aimed at distributing the inflow evenly. Even though the detail structures vary from one design to another, the principle for different inflow control devices is the same -restrict flow by creating additional pressure drop, and therefore balancing or equalizing wellbore pressure drop to achieve an evenly distributed flow profile along a horizontal well. With a more evenly distributed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 16 publications
0
32
0
Order By: Relevance
“…Further investigations revealed that this was due to the heel-toe effect (Daneshy, 2010). Different types of Inflow Control Devices are developed to delay early breakthrough by restricting the flow (Fernandes, 2009, Al-Khelaiwi, 2007. ICDs are designed to give a more uniform oil production along the horizontal well.…”
Section: Propertymentioning
confidence: 99%
“…Further investigations revealed that this was due to the heel-toe effect (Daneshy, 2010). Different types of Inflow Control Devices are developed to delay early breakthrough by restricting the flow (Fernandes, 2009, Al-Khelaiwi, 2007. ICDs are designed to give a more uniform oil production along the horizontal well.…”
Section: Propertymentioning
confidence: 99%
“…In this study, changes in reservoirs permeability are the matter of concern in terms of reservoir heterogeneity. Permeability difference is more likely to appear in long reservoirs, therefore, leading to non-uniform pressure distribution through the well and early water or gas breakthrough [3].…”
Section: Heterogeneitymentioning
confidence: 99%
“…The economical situation all around the world and the high availability of heavy oil recourses are the two main reasons which make these resources more valuable than ever before [1]. Horizontal drilling have been developed and utilized successfully during the past decades which enables more efficient production from long thin oil deposits by enhancing reservoir contact and thereby optimizing well performance [2][3][4][5]. However, there are still challenges regarding early water or gas breakthrough due to the frictional pressure drop along the well, reservoir heterogeneity and annular flow which impacts the production.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations